Iron deficiency across chronic inflammatory conditions: International expert opinion on definition, diagnosis, and management. Issue 10 (7th July 2017) - Cappellini, Maria Domenica; Comin‐Colet, Josep; de Francisco, Angel; Dignass, Axel; Doehner, Wolfram; S. P. Lam, Carolyn; Macdougall, Iain C.; Rogler, Gerhard; Camaschella, Clara; Kadir, Rezan; Kassebaum, Nicholas J.; Spahn, Donat R.; et al.
Abstract: Iron deficiency, even in the absence of anemia, can be debilitating, and exacerbate any underlying chronic disease, leading to increased morbidity and mortality. Iron deficiency is frequently concomitant with chronic inflammatory disease; however, iron deficiency treatment is often overlooked, partially due to the heterogeneity among clinical practice guidelines. In the absence of consistent guidance across chronic heart failure, chronic kidney disease and inflammatory bowel disease, we provide practical recommendations for iron deficiency to treating physicians: definition, diagnosis, and disease‐specific diagnostic algorithms. These recommendations should facilitate appropriate diagnosis and treatment of iron deficiency to improve quality of life and clinical outcomes.